PENERAPAN COGNITIVE BEHAVIOR THERAPY DALAM PENGURANGAN PROKRASTINASI AKADEMIK MAHASISWA - Pramitha Aulia; Achmad Gimmy Prathama; Tutty I Sodjakusumah (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This study aimed to test the application of Cognitive Behavior Therapy (CBT) in decreasing academic procrastination of college student. The experiment design was quasi-experimental pretest-posttest design. The effect of CBT in decreasing academic procrastination of college student was analyzed by comparing pretest and posttest results by Wilcoxon test. In the other hand, the qualitative data were collected by interview and analyzed by content analysis. The results was Cognitive Behavior Therapy (CBT) was able to improve the unhelpful rules that can lower academic procrastination behavior.